1989
DOI: 10.1084/jem.170.3.711
|View full text |Cite
|
Sign up to set email alerts
|

Strain dependency of B and T lymphoma development in immunoglobulin heavy chain enhancer (E mu)-myc transgenic mice.

Abstract: The involvement of dysregulated c-myc expression has been well established in certain virus-or chemical-induced and naturally developing tumors (1-5). Most of murine plasmacytomas and human Burkitt's lymphomas have been shown to carry a chromosomal translocation involving c-myc and Ig genes (2-5). In such tumor cells, only the c-myc transcripts from the translocated allele are constitutively expressed, while the normal allele is completely suppressed, suggesting that the translocation affects the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…6,7) We previously produced transgenic mice by introducing Eµ (immunoglobulin heavy chain enhancer)-myc gene into two inbred strains of mice, C57BL/6J (B6) and C3H/HeJ (C3H). 8) By analyses of these transgenic mice we found that most B6 transgenic mice developed B cell lymphomas while T cell lymphomas developed in most C3H transgenic mice. Furthermore, the average age of onset in inbred strains of mice is much earlier than in outbred strains.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…6,7) We previously produced transgenic mice by introducing Eµ (immunoglobulin heavy chain enhancer)-myc gene into two inbred strains of mice, C57BL/6J (B6) and C3H/HeJ (C3H). 8) By analyses of these transgenic mice we found that most B6 transgenic mice developed B cell lymphomas while T cell lymphomas developed in most C3H transgenic mice. Furthermore, the average age of onset in inbred strains of mice is much earlier than in outbred strains.…”
mentioning
confidence: 91%
“…8,9) The C3H Eµ-myc 24 line was chosen because offspring were obtained only from this line. The F 1 hybrid Eµ-myc mice were obtained by crossing C3H/HeJ transgenic mice with either B6 or BALB/c mice (Clea Japan, Inc., Tokyo).…”
Section: Methodsmentioning
confidence: 99%
“…In the mice injected subcutaneously with methylcolanthrene, the allelotype of aryl hydrocarbon hydroxylase locus determines whether the tumours are lymphomas or sarcomas at the injection site (Duran-Reynals, 1978). Eµ-myc transgene induce B-lineage lymphomas (Harris et al, 1988) in many mouse strains but in C3H, T-lymphomas occur predominantly (Yukawa et al, 1989), although the host gene responsible has not been identified. Similar genetic determination of T-lymphomas is also indicated in rats (Shisa and Hiai, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…For example, initogenic stimulation or chemically induced differentiation of certain cell lines results in changes in the levels of c-myc, c-myb, and c-fos proto-oncogenes (5,9,12,15,19,26,31). A constitutively high level of c-myc gene is detected in Burkitt's lymphoma cells (4) and development of B and T lymphoma is observed in Ey-mrc transgenic mice (37).…”
Section: Discussionmentioning
confidence: 99%